Problems Faced by Judges in Determining Rehabilitation for Narcotics Abusers - Tobing, Christina Natal Megawati; Hutapea, Tumbur Palti D. (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Addicts and victims of narcotic abuse should be placed in medical and social rehabilitation institutions. However, in empirical practice in the field, judges rarely exercise their powers to dive into a drug abuser accused of being brought to court through an assessment instrument. An assessment is needed to determine whether the defendant has a network of dealers or is just an addict or victim of narcotics abuse. The focus of this research problem is the obstacle for judges in determining the implementation of rehabilitation for narcotics abusers. The purpose is to identify the judge, in his decision, can determine medical rehabilitation for drug abusers in accordance with the mandate of the law. This research uses normative legal method based on positive legal studies with secondary data. The judge can consider whether the assessment results from the Integrated Assessment Team (TAT) allow them to be attached to the case file. Even the results of the assessment can be equated with expert testimony, which is an expert opinion written in a letter.